The effect of the symmetric and asymmetric stretching vibrations of CH4 on the O(3P) + CH4 → OH + CH3 reaction - Palma, J; Clary, D (2000)
We present a four-dimensional quantum scattering model to treat reactions of the type CH4 + X → CH3 + XH. The most important feature of the model is that it allows the effect of the symmetric and asymmetric stretching vibrations of CH4 on reactivity to be studied. We used the model to study the CH4 + O(3P) → CH3 + OH reaction. We found that the symmetric stretch vibration is more efficient in promoting reaction than the asymmetric stretch. We also found that exciting any of these stretching modes produces an inverted population in the umbrella vibration of product CH3 while, for the reactants in the ground state, the population is non-inverted.